2019
DOI: 10.1371/journal.pcbi.1006962
|View full text |Cite
|
Sign up to set email alerts
|

A system-wide network reconstruction of gene regulation and metabolism in Escherichia coli

Abstract: Genome-scale metabolic models have become a fundamental tool for examining metabolic principles. However, metabolism is not solely characterized by the underlying biochemical reactions and catalyzing enzymes, but also affected by regulatory events. Since the pioneering work of Covert and co-workers as well as Shlomi and co-workers it is debated, how regulation and metabolism synergistically characterize a coherent cellular state. The first approaches started from metabolic models, which were extended by the re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 74 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…For biological systems, where the knowledge about interactions of biological entities is more complete than for human cells, e.g., bacteria, it has been shown that the precise interplay of genetic regulation and metabolism installs a balance between robustness to environmental fluctuations and sensitivity to genetic changes 41 43 . By adjusting the ratio between AND and OR gates we can continuously tune our model to such a robust or sensitive behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…For biological systems, where the knowledge about interactions of biological entities is more complete than for human cells, e.g., bacteria, it has been shown that the precise interplay of genetic regulation and metabolism installs a balance between robustness to environmental fluctuations and sensitivity to genetic changes 41 43 . By adjusting the ratio between AND and OR gates we can continuously tune our model to such a robust or sensitive behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression regulates metabolism, which, in turn, modulates transcription, translation and degradation rates as well as the activity of transcription factors ( Covert et al , 2008 ). These processes interplay in networks of molecular interactions between DNA, RNA, proteins and metabolites ( Grimbs et al , 2019 ; Hernández-Prieto et al , 2014 ). Here, we aimed to perform the integrative modeling of transcription, translation, regulation of gene expression, metabolism and genome architecture, which is considered a prototype whole-cell model ( Szigeti et al , 2018 ).…”
Section: Approachmentioning
confidence: 99%
“…With emerging technologies to synthesize chromosomes from scratch, multiple gene regulation codes can be partitioned and programmed into cells. 1,2 Such a system could have orthogonal regulation encoded in different genomic regions while sharing common core machinery like transcription. 3,4 Gene regulation in bacteria is governed at the global and local levels.…”
Section: Introductionmentioning
confidence: 99%